2023
DOI: 10.3390/jcm12165352
|View full text |Cite
|
Sign up to set email alerts
|

No Benefits in Using Magnetically Controlled Growing Rod as Temporary Internal Distraction Device in Staged Surgical Procedure for Management of Severe and Neglected Scoliosis in Adolescents

Pawel Grabala,
Kelly Chamberlin,
Michal Grabala
et al.

Abstract: Background: Severe spinal curvatures (SSCs) in children and adolescents have long been treated with preoperative Halo traction, in its various variations. There are also several radical techniques available for the management of neglected SSCs, such as osteotomies; however, these can be risky. Comparing the treatment outcomes when using preoperative Halo Gravity Traction (HGT) against the use of a Magnetically Controlled Growing Rod (MCGR) as a temporary internal distraction (TID) device, we evaluated the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Additionally, it aids in enhancing lung function by 9% [10,15,32,34,35], an outcome that aligns with those observed in our study's Group 1 patients. A notable benefit of HGT therapy is its cost-effectiveness, requiring fewer financial investments compared with implant utilization or the application of magnetically controlled growing rods for internal temporary traction, as discussed in various studies [11][12][13][14]20]. Nevertheless, a direct comparison of overall treatment expenses is challenging due to variations influenced by a country's healthcare system and insurance framework.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, it aids in enhancing lung function by 9% [10,15,32,34,35], an outcome that aligns with those observed in our study's Group 1 patients. A notable benefit of HGT therapy is its cost-effectiveness, requiring fewer financial investments compared with implant utilization or the application of magnetically controlled growing rods for internal temporary traction, as discussed in various studies [11][12][13][14]20]. Nevertheless, a direct comparison of overall treatment expenses is challenging due to variations influenced by a country's healthcare system and insurance framework.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to external traction techniques that use Halo traction, we can use internal traction-the TID method-in various configurations [16,19,20,24,[40][41][42]. We found that one study compared the outcomes of a Halo gravity traction course with temporary internal distraction [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations